2013
DOI: 10.7482/0003-9438-56-089
|View full text |Cite
|
Sign up to set email alerts
|

Lactation curve of Beetal goats in Pakistan

Abstract: Abstract. This study was accomplished with the objective to determine parameters of lactation curves in Beetal goats using Wood’s model. Therefore, milk yield data on 127 Beetal goats maintained at five different government farms were recorded from post-kidding to drying off of does. Wood model parameters were estimated using non-linear regression and individual curves were fitted. The characteristics/parameters of lactation curve were computed. The mean initial yield »a«, rate of increase »b« and rate of decl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
1
7
1
Order By: Relevance
“…This estimate is higher than the means of 0.08 kg/week and 0.005 kg/week that demonstrated by Ayasrah et al (2013) and Siqueira et al (2017) of Damascus goats in Jordan and of dairy goats in Brazil, respectively. Conversely, the obtained estimate is lower than that of 0.12 kg/week reported by Takma et al (2009) and Waheed and Khan (2013) of Bornova goats in Turkey and Beetal goats in Pakistan, respectively. Within each classification in the same column, means followed by different superscript letters differ significantly; ** (P<0.01); NS: not significant; Parameter (a): the initial milk yield (kg) after kidding; Parameter (b): the rate of rise in milk production to peak lactation (kg/week); Parameter (c): the rate of decrease in milk production from peak to the end of lactation (kg/week).…”
Section: Lactation Curve Traitscontrasting
confidence: 82%
See 1 more Smart Citation
“…This estimate is higher than the means of 0.08 kg/week and 0.005 kg/week that demonstrated by Ayasrah et al (2013) and Siqueira et al (2017) of Damascus goats in Jordan and of dairy goats in Brazil, respectively. Conversely, the obtained estimate is lower than that of 0.12 kg/week reported by Takma et al (2009) and Waheed and Khan (2013) of Bornova goats in Turkey and Beetal goats in Pakistan, respectively. Within each classification in the same column, means followed by different superscript letters differ significantly; ** (P<0.01); NS: not significant; Parameter (a): the initial milk yield (kg) after kidding; Parameter (b): the rate of rise in milk production to peak lactation (kg/week); Parameter (c): the rate of decrease in milk production from peak to the end of lactation (kg/week).…”
Section: Lactation Curve Traitscontrasting
confidence: 82%
“…PMY was calculated as PMY, kg = a (b/c) b e -b , and PW, weeks was calculated as PW = b/c. Persistency of lactation (P, %) was calculated as P % = Milk L/Milk F * 100, where Milk L is milk production after peak and Milk F is milk production before the peak (Waheed and Khan, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This goat has a great adaptability to produce high quality and high volume of milk in desert zones reaching between 0.95 to 1.561 Kg of milk per day during first lactation period using early goats (1-2 years old) and around 1.640 Kg of milk per day using mature goats (3 to 7 biological years) (Maltz and Shkolnik, 1980). A similar result was described for Beetel goat in Pakistan, where mature goats produce more milk than early goats during first lactation period (Waheed and Khan, 2013). Regarding milk quality in Black Bedouin goat, during its first four lactation periods, the content of protein, fat and lactose were stable and around of 3.5%, 5.5% and 5%, respectively (Shkolnik et al, 1980).…”
Section: High Milk Quality Another Challenge For Goat Breeding In Arsupporting
confidence: 64%
“…Besides, they showed that type of birth and age of the doe affected the lactation curve, but not the parity and the sex of the kids. In fact, they proposed that from lactation curve is possible to evaluate the performance of each doe, take decision about the renewal of the herd or make changes in the management procedures to improve milk production (Waheed and Khan, 2013).…”
Section: Lactation Periodsmentioning
confidence: 99%